ACTIVITY OF CROWDFUNDING PLATFORMS IN UKRAINE: REGIONAL ASPECT (World of finance, 2022)
Introduction. There are several crowdfunding platforms in Ukraine, which are dynamically developing and helping authors to find investors.The purpose of the article is to analyze the activities of crowdfunding platforms in Ukraine and identify regional features on the example of the platform “Big Idea”.Methods. Methods of analysis and comparison, rating assessment, theoretical generalization are used.Results. The financial aspects of placing projects on the crowdfunding platforms “Big Idea”, “GoF” and “RazomGO”, and the results of their activities in terms of successfully implemented projects, attracting investors and funds are considered. Based on the data of the platform-leader “Big Idea” for 2015–2021, forecast trend models were built. The zoning of the regions of Ukraine was carried out on the basis of their ratings according to the indicators of successfully implemented projects and their investors on the platform “Big Idea”.Conclusions. It was found that the leaders in the number of successfully implemented projects and their investors on the platform “Big Idea” are Kyiv, Lviv and Kharkiv regions, outsiders – Transcarpathian and Sumy regions, Crimea.